2007
DOI: 10.1089/jpm.2006.0150
|View full text |Cite
|
Sign up to set email alerts
|

Rational Use of Sublingual Opioids in Palliative Medicine

Abstract: The sublingual administration of opioid analgesics has been a mainstay in the pain management of homebound dying hospice patients who are no longer able to swallow. It is also a potentially useful route of administration in other situations in which the oral route is not available and other routes are impractical or inappropriate. Potential advantages of the sublingual route include rapid analgesic onset and avoidance of hepatic first-pass metabolism. Pharmacokinetic and pharmacodynamic studies have yielded wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 69 publications
0
31
0
Order By: Relevance
“…Pharmacokinetic data indicated that blood levels of morphine following sublingual administration do not rise faster than those following oral administration. In a more recent review, Reisfield & Wilson [90] supported the conclusions of Coluzzi [99] regarding morphine and extended these conclusions to oxycodone and hydromorphone as well. No studies of the use of sublingual morphine in non‐hospice palliative care patients were identified.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Pharmacokinetic data indicated that blood levels of morphine following sublingual administration do not rise faster than those following oral administration. In a more recent review, Reisfield & Wilson [90] supported the conclusions of Coluzzi [99] regarding morphine and extended these conclusions to oxycodone and hydromorphone as well. No studies of the use of sublingual morphine in non‐hospice palliative care patients were identified.…”
Section: Resultsmentioning
confidence: 71%
“…Cautions and Considerations Disadvantages of this route include bitter taste, burning sensation, possible ulceration, and need to retain the drug sublingually for several minutes [16,[89][90][91]99]. Patients are required to avoid eating or drinking until the medication has been completely dissolved.…”
Section: Sublingualmentioning
confidence: 99%
“…in less than 15 min. In case of sublingual spray, the drug is readily available in dissolved form and upon spray as fine mist, rapidly absorbs into systemic circulation [3]. Rapid pharmacological response is highly desirable in certain cases such as breakthrough pain.…”
Section: Sublingual Deliverymentioning
confidence: 99%
“…Interest in noninvasive but fast-acting formulations for opioid administration has generated investigation of the sublingual route 7,8. Compared with the transmucosal and buccal routes, the sublingual route may be even more attractive for fentanyl delivery 911.…”
Section: Introductionmentioning
confidence: 99%